HUBUNGAN LAMA PENGGUNAAN VENTILATOR MEKANIK DENGAN KEJADIAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) PADA PASIEN PERAWATAN DI ICU RSUP PERSAHABATAN JAKARTA PERIODE 2018-2019 - Amalia Shinta Ayunani, (2020)
Mechanical ventilator is a form of life supporting device provided for the patients in ICU with various comorbid diseases. However the use of mechanical ventilators can also bring up the risk of other complications for its users. One of the example is ventilator-associated pneumonia (VAP). Many factors were suspected to affect the incidence of VAP. One of the example is the duration of mechanical ventilator use. This study aims to determine the correlation between the length of mechanical ventilator use to the incidence of ventilator-associated pneumonia (VAP) on the ICU treated patients of Persahabatan Hospital Jakarta. This study uses the observational analytic methodes with cross sectional design. Sampling was done by consecutive sampling technique. This study uses secondary data from medical records of the ICU treated patients of Persahabatan Hospital Jakarta by the period of 2018-2019. The samples used in this study consist of 37 ICU patients, 13 patients were diagnosed with VAP and 24 others were not diagnosed with VAP. From the correlation test, the obtained p value is 0,001 (p<0,05). Hence, it could be concluded that there was a significant relation between the duration of mechanical ventilator use with the incidence of VAP on the ICU treated patients of Persahabatan Hospital Jakarta by the period of 2018-2019.